2010
DOI: 10.1007/s00262-010-0931-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of TLR3, TLR4, and TLR9 in prostate carcinomas and their association with biochemical recurrence

Abstract: TLR expression is associated with prostate cancer with recurrence and the role of TLR receptors in the biology of malignancy merits study. Therapeutic strategies to boost or block TLRs may be of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 57 publications
2
95
0
Order By: Relevance
“…At the tissue level, TLRs have been reported to be up-regulated by prostate cancer cells as assessed by IHC. For example, TLR3, TLR4, and TLR9 were shown to be produced by prostate tumor cells as assayed by IHC, and interestingly, high expression of these TLRs as assayed by real-time PCR was found to correlate with biochemical recurrence (Gonzalez-Reyes et al 2011). The mechanism by which this relationship may arise, however, remains unclear, as, on the contrary, TLR stimulation in cancer cells in prostate cancer models has also been consistently shown to result in the upregulation of inflammatory cytokines and induction of apoptosis and/or anti-tumor immune responses (Paone et al 2008;Harashima et al 2012;Chin et al 2010;Galli et al 2010;Andreani et al 2007).…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 96%
“…At the tissue level, TLRs have been reported to be up-regulated by prostate cancer cells as assessed by IHC. For example, TLR3, TLR4, and TLR9 were shown to be produced by prostate tumor cells as assayed by IHC, and interestingly, high expression of these TLRs as assayed by real-time PCR was found to correlate with biochemical recurrence (Gonzalez-Reyes et al 2011). The mechanism by which this relationship may arise, however, remains unclear, as, on the contrary, TLR stimulation in cancer cells in prostate cancer models has also been consistently shown to result in the upregulation of inflammatory cytokines and induction of apoptosis and/or anti-tumor immune responses (Paone et al 2008;Harashima et al 2012;Chin et al 2010;Galli et al 2010;Andreani et al 2007).…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 96%
“…Likewise, we found that samples of prostate carcinomas with recurrence exhibited a significant increase in the mRNA levels of TLR3, TLR4 and TLR9. In addition, the tumors that showed high level expression of TLR3 or TLR9 were significantly associated with higher probability of biochemical recurrence [66] . However, we also found that breast tumors with high TLR9 expression by fibroblast-like cells were associated with a low metastasis rate.…”
Section: Clinical Relevance Of Inflammatory Components In Tumor Progrmentioning
confidence: 98%
“…This was established by immunohistochemistry on tumor tissue sections of breast carcinoma [25], oral squamous cell carcinoma [26], cervical carcinoma [27], ovarian carcinoma [28], prostate carcinoma, head and neck carcinoma [29]. Furthermore, the level of TLR3 expression by prostate cancer cells was shown to be significantly associated with higher probability of biochemical recurrence [30]. We have also observed TLR3 staining on lung squamous cell carcinoma and on a portion of HCC (our unpublished data).…”
Section: Inflammatory and Proliferative Responses Of Cancer Cellsmentioning
confidence: 82%